2017
DOI: 10.21608/sjfop.2017.11322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio-Fertilization and Growing Media on the Chemical Composition of Moringa Oleifera Trees

Abstract: during two successive seasons of 2014 and 2015 to study the effect of growing media (sand, clay and mixture (sand + clay at 1:1 v/v) and bio-fertilization (microbine, green power and potasiomag) with 200 ml/pot on the chemical composition of Moringa oleifera (chlorophyll a, b, a + b, carotenoids, carbohydrates and mineral elements (N, P and k %). The results showed that the highest leaf contents of chlorophyll a, b and carotenoids, carbohydrates and leaf N, P and K % were obtained from the most suitable media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The combined application between sand and clay soil provides adequate nutrients for I. edulis seedlings and enhancements both the physical and biological properties of growing media and water uptake capacity with its content from nutrients which reflected on increase metabolic processes efficiency and improving the leaves mineral content of the seedlings. Sarhan et al (2017) showed that the highest leaf contents of chlorophyll a, b, leaf N, P, and K % were obtained from the most suitable media (sand + clay at 1:1 v/v). Also, Abd El ghafour et al (2009) revealed that all chemical fertilization treatments increased N, P, and K percent in leaves as compared with control plants.…”
Section: Growing Media and Npk Effects On The Chemical Constitutes Of I Edulis Leavesmentioning
confidence: 98%
“…The combined application between sand and clay soil provides adequate nutrients for I. edulis seedlings and enhancements both the physical and biological properties of growing media and water uptake capacity with its content from nutrients which reflected on increase metabolic processes efficiency and improving the leaves mineral content of the seedlings. Sarhan et al (2017) showed that the highest leaf contents of chlorophyll a, b, leaf N, P, and K % were obtained from the most suitable media (sand + clay at 1:1 v/v). Also, Abd El ghafour et al (2009) revealed that all chemical fertilization treatments increased N, P, and K percent in leaves as compared with control plants.…”
Section: Growing Media and Npk Effects On The Chemical Constitutes Of I Edulis Leavesmentioning
confidence: 98%
“…Based on the post hoc test (Table 3) it is known, only F4 that has significantly different effects from the other 3 treatments (F1, F2, F3). This means that NPK-fertilizer had a significant effect on the kelor seedling's diameter growth and was significantly different from no fertilization treatment [16,17]. The post hoc test result is presented in Table 3.…”
Section: Diametermentioning
confidence: 89%
“…But at 3 MAS, the value of F1 was significantly different from the others, the value is the lowest. Fertilization using low dose of NPK has a significant effect on the height variable of young plants or seedlings [13,14], but excessive fertilization will actually reduce the plant growth performance [15,16].…”
Section: Heightmentioning
confidence: 99%